2022
DOI: 10.1177/14799731221133387
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography-based body composition measures in COPD and their association with clinical outcomes: A systematic review

Abstract: Background Computed tomography (CT) is commonly utilized in chronic obstructive pulmonary disease (COPD) for lung cancer screening and emphysema characterization. Computed tomography-morphometric analysis of body composition (muscle mass and adiposity) has gained increased recognition as a marker of disease severity and prognosis. This systematic review aimed to describe the CT-methodology used to assess body composition and identify the association of body composition measures and disease severity, health-rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 82 publications
0
1
0
Order By: Relevance
“…Moreover, additional evidences on the role of changes of WAT in cancer have been obtained by retrospective studies conducted among gastrointestinal cancers and in hematological diseases [35–39,40 ▪ ,41–43]. Also, a systematic review including studies on COPD showed a link between changes in adiposity and cardiovascular diseases [44].…”
Section: Clinical Impact Of Adipose Tissue Wasting In Cachexiamentioning
confidence: 99%
“…Moreover, additional evidences on the role of changes of WAT in cancer have been obtained by retrospective studies conducted among gastrointestinal cancers and in hematological diseases [35–39,40 ▪ ,41–43]. Also, a systematic review including studies on COPD showed a link between changes in adiposity and cardiovascular diseases [44].…”
Section: Clinical Impact Of Adipose Tissue Wasting In Cachexiamentioning
confidence: 99%
“…Emerging tools include CT-morphometric measurement for structure-function associations and CT-quantitative analysis of muscle mass and adipose tissue for assessing disease severity and prognosis in COPD with sarcopenia. 9,10 The literature on COPD with sarcopenia encompasses comprehensive reviews, system reviews, and meta-analysis covering relevance, 11,12 mechanisms, 13 prevalence, 14,15 diagnosis and treatment, 16 and even pathogenesis based Chinese traditional medicine theory. 17,18 However, a notable gap exists in a comprehensive scientometric analysis of the existing literature.…”
Section: Introductionmentioning
confidence: 99%